Influence of a custom-made maxillary mouthguard on gas exchange parameters during incremental exercise in amateur road cyclists - Piero, M.; Simone, U.; Jonathan, M.; Maria, S.; Giulio, G.; Francesco, T.; Gabriella, C.; Laura, A.; Eva, B.; Gianni, M.; Francesco, C.; Giovanni, G. (The Journal of Strength and Conditioning Research, 2015)
Mouthguards are frequently used for protection purposes, particularly by athletes competing in contact sports. However, there is increasing evidence supporting their use for improving performance. Studies have focused their use in athletes who do not traditionally use mouthguards and who may be looking for a performance edge. The aim of the current study was to evaluate the influence of a custom-made mouthguard (Parabite Malpezzi, PM) on maximal and submaximal physiological parameters related to performance in road cycling. Ten well-trained amateur road cyclists (34 ± 6 years) performed an incremental cardiopulmonary exercise test to exhaustion on a frictional braked cycle ergometer. Work rate (WR), heart rate, oxygen consumption (VO2) , carbon dioxide production, and ventilation at the lactate threshold, at the respiratory compensation point (RCP), and at maximal exercise (MAX) were determined in normal conditions (C) and wearing PM. Cycling economy was also evaluated by analyzing the slope of the VO2/WR (dVO2)/dWR, in milliliters per watt per minute) relationship during the test. Wearing the PM compared with C resulted in significant increases in WR at RCP (281 ± 32 vs. 266 ± 19 W, p = 0.04) and at MAX (353 ± 44 vs. 339 ± 38 W, p = 0.004). The PM also resulted in an average 8% lower dVO2/dWR (9.5 ± 1.1 vs. 10.3 ± 1.1 ml/W/min, p = 0.06) but did not significantly modify any of the other measured parameters at LT, RCP and MAX. To the best of our knowledge, this study is the first to evaluate the effects of a dentistry-designed mouthguard on physical performance of road cyclists. These results provide support for cyclists to correct jaw posture that may improve their exercise performance.